2019
DOI: 10.1126/sciadv.aau4506
|View full text |Cite
|
Sign up to set email alerts
|

Quantizing single-molecule surface-enhanced Raman scattering with DNA origami metamolecules

Abstract: Tailored metal nanoclusters have been actively developed to manipulate light at the subwavelength scale for nanophotonic applications. Nevertheless, precise arrangement of molecules in a hot spot with fixed numbers and positions remains challenging. Here, we show that DNA origami metamolecules with Fano resonances (DMFR) can precisely localize single dye molecules and produce quantified surface-enhanced Raman scattering (SERS) responses. To enable tailored plasmonic permutations, we develop a general and progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
129
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(129 citation statements)
references
References 42 publications
0
129
0
Order By: Relevance
“…S8 the Raman spectra of each step (in Fig. 1) with a 633 nm laser are shown 49,50,64,81,82 . At Raman shift between 1000 and 1700 cm -1 , we can observe the Raman peak of Au NP, which was invisible in the case of pristine graphene.…”
Section: Nanoscale Advances Accepted Manuscriptmentioning
confidence: 99%
“…S8 the Raman spectra of each step (in Fig. 1) with a 633 nm laser are shown 49,50,64,81,82 . At Raman shift between 1000 and 1700 cm -1 , we can observe the Raman peak of Au NP, which was invisible in the case of pristine graphene.…”
Section: Nanoscale Advances Accepted Manuscriptmentioning
confidence: 99%
“…www.advmat.de www.advancedsciencenews.com metamolecules have inspired various experimental studies on the self-assembly of metallic colloidal clusters, as summarized in the next section. [28][29][30][31][32][33][34]39,40,[44][45][46][47][48][49][100][101][102][103]…”
Section: Design Of Plasmonic Metamoleculesmentioning
confidence: 99%
“…The experimental observations of optical magnetism reported to date are still limited to the discrete unit of the well-assembled, individual 2D trimer, 2D tetramer, and 3D tetrahedral cluster. [28][29][30][31][32][33][34]39,40,[100][101][102][103] The advance in dark-field microscopic analyses has enabled these observations of magnetism from a single metamolecule. [176] This problem mainly originates from (i) low assembly yield and (ii) low robustness of the resonant modes against a few nanometer-error in the structures.…”
Section: Practical Limits Of Molecular Motifsmentioning
confidence: 99%
“…In response to the urgent need to develop new and more reliable detection methods, currently some recent advances in nanosensing have opened up new opportunities for developing novel optical and electrical methods for DENV detection, such as fluorescence [ [23] , [24] , [25] ], surface plasmon resonance (SPR) [ 26 ], surface-enhanced Raman spectroscopy (SERS) [ 27 , 28 ], and electrochemistry [ 29 , 30 ]. Among them, SERS as a molecular fingerprint spectrum which can achieve ultrasensitive detection even to single molecular level is considered to be a potential and powerful analysis tool [ [31] , [32] , [33] ]. For instance, Huh et al reported an on-chip SERS by integrating capture probe immobilized AuNPs and dye labeled target DNA for the detection of DENV-related nucleic acid sequences with a detection limit of 30 pM [ 34 ].…”
Section: Introductionmentioning
confidence: 99%